Identification of safe airspace above waterways by Monte Carlo simulation - Choo, Megan Ming-Hui (Nanyang Technological University, 2024)
This report presents a comprehensive study of the applications of Monte Carlo simulation in determining a safe airspace boundary for drone motion above waterways. More specifically, it involved path planning, conducting thousands of simulations of drone trajectories, determining an appropriate risk tolerance to demarcate a safe waterway boundary, and finally, determining the necessary boundary width for safe drone motion.